Acute myocardial infarction triggered by use of synthetic cannabis. Issue 2 (3rd April 2018) - Mills, Brooke; Dishner, Emma; Velasco, Carlos E.
ABSTRACT: A young woman presented with an anterior ST elevation myocardial infarction shortly after synthetic cannabis use. This report highlights the cardiovascular risks of these drugs.